Genetic Population Structure and Demographic History of the Widespread Common Shipworm Teredo navalis Linnaeus 1758 (Mollusca: Bivalvia: Teredinidae) in European Waters Inferred from Mitochondrial COI Sequence Data - Weigelt, Ronny; Lippert, Heike; Karsten, Ulf; Bastrop, Ralf (Frontiers in Marine Science, 2017)
The first documented scientific reports of the common marine shipworm Teredo navalis (Bivalvia) for Central Europe waters date back to the time between 1700 and 1730 in the Netherlands. During the following centuries there were several irregular mass occurrences reported for both the North Sea and the Baltic Sea. These events were accompanied by massive destruction of wooden ships and coastal protection structures. In this study, the first population analysis of T. navalis is presented with the aim to detect the genetic population structure in the waters of Central Europe. The mtDNA COI (cytochrome c oxidase subunit I) locus was found as suitable molecular marker and hence a 675 bp gene fragment was studied. A total of 352 T. navalis specimens from 13 different sampling sites distributed across Central Europe were examined. Subsequently, various population genetic indices including FST values and an AMOVA analysis were applied for the description of the population structure. To visualize the distribution of haplotypes at the different sampling sites two median-joining networks were calculated. In addition, the past demographic structure of the T. navalis population was analyzed, among others by calculating Tajima´s D, Fu´s F and the mismatch distribution. Finally, all computations of the population genetic indices could not reveal differentiated populations or any kind of distinct population structure in T. navalis. The network analyses revealed ‘star-like’ patterns without differentiated substructures or demes. Therefore, it can be assumed that a sudden expansion of this species took place without any indications of neither a bottleneck nor a founder effect for the study area. The results of this study support the concept of a regional panmictic population in the waters of Central Europe with unhindered migration of individuals (e.g. via pelagic larvae) between the various sampling sites as reflected by a high gene flow.